Aqueous biphasic systems using chiral ionic liquids for the enantioseparation of mandelic acid enantiomers - e Silva, Francisca A. (2020)
This work aims at extending the applicability of chiral aqueous biphasic systems (ABS) to enantioseparations by using chiral ionic liquids (CILs) simultaneously as phase forming agents and chiral selectors. After determining the ternary phase diagrams of ABS composed of CILs and salts, these were used to ascertain the CIL structure and salt role on the ABS aptitude to separate mandelic acid enantiomers. Representative CIL-based ABS were further employed in optimization studies, where the mandelic acid content, temperature, tie-line length, salt and phases weight ratio were studied. The influence of these parameters is shown to be highly dependent on the CIL-based ABS, nevertheless the results here reported suggest that the key driving the enantioseparation in these ABS is a combination of the enantiorecognition ability of a given CIL with the solubility of mandelic acid in the corresponding CIL-rich phase.